Enhancement of the Jovian Magnetospheric Plasma Circulation Caused by the Change in Plasma Supply From the Satellite Io. Issue 8 (18th August 2018) - Tsuchiya, F.; Yoshioka, K.; Kimura, T.; Koga, R.; Murakami, G.; Yamazaki, A.; Kagitani, M.; Tao, C.; Suzuki, F.; Hikida, R.; Yoshikawa, I.; Kasaba, Y.; et al.
Abstract: The innermost Galilean satellite, Io, supplies a large amount of volcanic gasses to the Jovian magnetosphere. The fast rotation of Jupiter and the outward transport of ionized gasses are responsible for forming a huge and rotationally dominant magnetosphere. The plasma supply from the satellite has a key role in the characterization of the Jovian magnetosphere. In fact, significant variations of the plasma population in the inner magnetosphere caused by the volcanic eruptions in Io were found in early 2015, using a continuous data set of the Io plasma torus obtained from an extreme ultraviolet spectroscope onboard the Hisaki satellite. The time evolution of the Io plasma torus radial distribution showed that the outward transport of plasma through 8 R J from Jupiter was enhanced for approximately 2 months (from the end of January to the beginning of April 2015). Intense short‐lived auroral brightenings––which represent transient energy releases in the outer part of the magnetosphere—occurred frequently during this period. The short‐lived auroral brightenings accompanied well‐defined sporadic enhancements of the ion brightness in the plasma torus, indicating a rapid inward transport of energy from the outer part of the magnetosphere and the resultant enhancement of hot electron population in the inner magnetosphere. This evidently shows that the change in a plasma source in the inner magnetosphere affects a large‐scale radial circulation of mass and energy in a rotationally dominant magnetosphere. Plain Language Summary: We present the first continuous and long‐term monitoring of both ultraviolet aurora activity and ionized gas around Jupiter obtained by the Earth‐orbiting spectroscope satellite, Hisaki. The innermost Galilean satellite, Io, is the volcanically most active body in our solar system. The volcanic gasses are ionized in the magnetosphere, the region manipulated by the planetary magnetic field, and obtain angular momentum from Jupiter's fast rotation through the magnetic field connecting with Jupiter. When Io's volcanic activity increased in early 2015, Hisaki observed that the Jovian magnetosphere was filled with iogenic ionized gasses for over 2 months and Jupiter's powerful auroral breakups occurred very frequently. This is contradictory to the terrestrial magnetosphere in which the aurora breakup occurs as a result of the solar wind‐energy penetration into the magnetosphere. Although Io occupies only a very small region in the vast Jovian magnetosphere, it releases significant amounts of material around the space near Jupiter, extracts energy from Jupiter's rotation, and affects activation of the powerful aurora of the giant planet. Key Points: Evolution of Io plasma torus radial distribution caused by volcanic eruptions in Io was observed in early 2015 Outward plasma transport from the Io plasma torus through 8 R J from Jupiter enhanced for approximately 2 months An inner magnetosphere plasma source is shown to affect large‐scale mass/energy radial circulation in rotationally dominant magnetosphere